Stick Dog gets the tacos - Watson, Tom, 1965- (Watson, Tom, 1965- Stick Dog, 2019)
As a family of humans plans to feast on tacos, tortilla chips, and guacamole, Stick Dog sees a great opportunity to feed his hungry canine friends.